2003
DOI: 10.1007/s12126-003-1007-7
|View full text |Cite
|
Sign up to set email alerts
|

Hidden in the household: Now it’s men in mid-life

Abstract: Both gender and ageing are being reconceptualized as contingent and more complex than previously thought. The architecture of gender as we age is transforming too, as the twin forces of globalization (leading simultaneously to homogeneity and diversity) and postmodern identity formation collide and intersect. Lives, relationships, and senses of self are textured by socioeconomic restructuring, by the uncertainties and insecurities of the global economy and global politics, and by enhanced social and social pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
(41 reference statements)
1
6
0
1
Order By: Relevance
“…The effect of loss of social contacts is likely to be more severe for older unemployed people compared with younger unemployed people since the developmental literature indicates that people tend less to develop new friendships with increasing age, instead deepening their existing ones with the assumption that they will remain their friends for life (Carstensen, 1995). The above passages support the conclusions of McDaniel (2003) about the socially isolating effect of middle‐aged unemployment.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The effect of loss of social contacts is likely to be more severe for older unemployed people compared with younger unemployed people since the developmental literature indicates that people tend less to develop new friendships with increasing age, instead deepening their existing ones with the assumption that they will remain their friends for life (Carstensen, 1995). The above passages support the conclusions of McDaniel (2003) about the socially isolating effect of middle‐aged unemployment.…”
Section: Resultssupporting
confidence: 81%
“…Encel, 1997; Sheen, 1999; Taylor, 2001), there has been very little research into the relationship between mature‐aged unemployment and psychological and financial outcomes for the individuals. Two exceptions are the work of McDaniel (2003) and a theoretical article by Warr (1997). McDaniel (2003) undertook a qualitative study of unemployed, white‐collar, Canadian, middle‐aged men and found that unemployment was a shock to their identity, resulting in them retreating from the world and ‘hiding’ at home.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For men it often is (van Tilburg, 2003). Consequently, many unemployed men are embarrassed to be seen in public not working or travelling to and from work and instead hide in the home, which they tend to regard as a woman's domain (McDaniel, 2003). Deprived of the provider role, they are unable to find a meaningful substitute in the short term, if ever.…”
Section: The Context: the Need To Increase Mature-aged Workforce Partmentioning
confidence: 99%
“…Les jeunes poursuivent leurs études plus longtemps ou travaillent à temps partiel avant de rallier le monde du travail rémunéré à plein temps. Les travailleurs vieillissants préfèrent la préretraite au chômage (Guillemard, 2000;Myles, 2002;McDaniel, 2003c;Myles et Pierson, 2001). Les catégories traditionnelles se brouillent : on peut être tout à la fois travailleur indépendant, préretraité, demandeur de travail et étudiant à temps partiel (McDaniel, 2003b).…”
Section: Philosophies Politiquesunclassified